PENGARUH KEPERCAYAAN JAWA DALAM PRAKTIK PERNIKAHAN BUDDHIS DI KABUPATEN SEMARANG - Tri Saputra Medhacitto (NALAR: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aims to explore the practice of Buddhist marriage in the Semarang Regency, which is carried out alongside traditions and local wisdom. The research employs a qualitative approach using a cultural anthropology method to examine the influence of Javanese beliefs on the wedding rituals of Buddhist communities in the Semarang Regency area. Data were collected through the review of relevant literature and interviews with selected informants, chosen based on their background and expertise related to the research topic. The collected data were then analyzed in depth to identify the values of local wisdom within Javanese society that coexist harmoniously with Buddhist wedding ceremonies. The findings indicate that Buddhist marriage in Semarang Regency is not merely a legal recognition of union between two individuals entering married life, but also represents a socio-cultural phenomenon reflecting processes of adaptation and negotiation between religious teachings and local cultural values. Buddhist communities in Semarang Regency conduct marriage ceremony according to Buddhist religious traditions combined with Javanese practices. The religious ceremony is performed at a temple and led by a Romo Pandita, and the the wedding ceremonies continue according to Javanese culture. Javanese beliefs remain strongly influential, shaping various stages of marriage, from partner selection and proposal rituals to ceremonial practices during the wedding. Beliefs related to weton calculations, auspicious days, slametan rituals, the preparation of sesajen, and ceremonial elements within wedding receptions continue to maintain their place amid the dynamics of modern society.